Characteristics of cytokines/chemokines associated with disease severity and adverse prognosis in COVID-19 patients - Cheng, Jianghao; Wang, Haozhen; Li, Chaodan; Yu, Jianhua; Zhu, Mingli (Frontiers in Immunology, 2024)
BackgroundCytokines and chemokines as crucial participants in innate immune response play significant roles during SARS-CoV-2 infection, yet excessive immune response exacerbates the severity of COVID-19.PurposeThis study aims to investigate the involvement of which cytokines/chemokines in the cytokine storm of COVID-19, as well as the changes in cytokine/chemokine levels during the course of COVID-19, simultaneously exploring the diagnostic and prognostic value of the relevant cytokines/chemokines for COVID-19.MethodsFlow cytometry was employed to detect the levels of cytokines and chemokines in the serum of 50 COVID-19 patients.ResultsCompared with severe COVID-19 patients, the levels of cytokines IL-6, IL-8, IL-10, sCD25, and chemokines IP-10 and MIG in the peripheral blood of non-severe patients were significantly reduced, while only IL-6, IL-10, and IP-10 levels were significantly decreased compared to non-survivors of COVID-19. Meanwhile, serum concentrations of IP-10, MCP-1, sTREM-1, IL-10, and the neutrophil-to-lymphocyte ratio (NLR) in peripheral blood could distinguish between COVID-19 survivors and non-survivors and were significantly associated with mortality. Among them, the concentration of IP-10 was shown to be the most powerful indicator for predicting adverse outcomes in COVID-19 patients (AUC: 0.715); however, its combined detection with the conventional inflammatory marker NLR did not improve the predictive value for adverse outcomes in COVID-19 patients. Additionally, serum IP-10 levels were negatively correlated with peripheral blood NK cell count and total lymphocyte count, while sTREM-1 levels were positively correlated with peripheral blood CD4+ T cell count and CD3+ T cell count. Meanwhile, IL-8 levels were positively correlated with total lymphocyte count in peripheral blood. Finally, the serum levels of cytokines/chemokines in non-survivors of COVID-19 increased significantly before death, while in survivors, they returned to normal levels before discharge.ConclusionsSeverely ill and non-surviving COVID-19 patients exhibit compromised immune function, with significantly higher levels of inflammation, cytokine/chemokine storms, and immune dysregulation compared to non-severe patients. Serum concentrations of IP-10, MCP-1, sTREM-1, and IL-10 levels can serve as biomarkers to predict adverse outcomes in COVID-19.